INTERACTIVE ALV REPORT CUSTOMIZATION OF BUSINESS PROCESS TRACING ON SAP S/4HANA WITH ITERATIVE AND INCREMENTAL METHODOLOGY IN TELECOMUNICATION COMPANY - Jasmine Aurely Salshabillah; Muhardi Saputra; Warih Puspitasari (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
PT XYZ is a State-Owned Enterprise (BUMN) that is focused on the telecommunications sector. To manage the ongoing business, the company uses SAP S/4HANA. In implementing SAP S/4HANA, several problems were found in the controlling module, particularly in the cost allocation process that occurred in Activity-Based Costing (ABC). The main problem is that it is difficult to track business processes in cost allocation activities so that the source and destination of the business processes are not known. Based on this problem, it will be the main reason for making the Interactive ALV Report for tracing business processes. This Interactive ALV report for tracing business processes will use ABAP Programming Module as the reference and Iterative and Incremental as the methodology. This business process tracing report will have a feature where users can track business processes from the source of the business process to the last business process. The result of this design is a tracing business process report that can display only the data needed by the finance division for the business process tracing process. This Interactive ALV report will help the finance division distribute costs in the cost allocation process. The results of this study are expected to provide benefits for PT XYZ and other companies that have the same problem or can add insight into ABAP programming, especially on the controlling module.